The drivers of digital transformation : why there's no way around the cloud (Springer, 2017)
Annotation In this book, leading CEOs, CIOs and experts from international corporations explore the role of digitalization and cloud-based processes as the main business drivers of the 21st century. Focusing on how to get started with digitalization and how to handle the technologies involved, they employ analyses and practical case studies to demonstrate how to unleash the potential offered by the cloud, and how to achieve the most critical success factors quality and security through the right partnerships. Readers will discover why the cloud will soon take over the driver s seat in cars, and why Heineken CIO Anne Teague claims that innovation is impossible without high-quality IT. The book reveals what IT managers can learn from Silicon Valley and China today, and why Deutsche Telekom CEO Tim Hoettges believes Europe s future depends on successful digitalization. In a closing strategic assessment, the editor Ferri Abolhassan presents the cloud as the essential backbone of digitalization. In short, the book provides readers the first comprehensive, high-level assessment of cloud-based digital transformation in the era of Industry 4.0."
Keywords: Information technology -- Management.; Cloud computing.; Business enterprises -- Technological innovations.; Electronic data processing.; elektronické knihy; electronic books